Handbook of Media for Environmental Microbiology - Atlas, Ronald M (Taylor & Francis, 2005)
"The Handbook of Media for Environmental Microbiology, Second Edition is a comprehensive guide to the nearly 2000 media that are used by environmental microbiologists to cultivate and maintain the ever-expanding diversity of microorganisms collected from soil, water, or air. It covers the entire range of media needed for environmental microbial analyses, for the isolation of microorganisms from soils and waters, and for the cultivation of environmentally relevant microorganisms, including plant pathogens." "All scientists who cultivate bacteria, archaea, and fungi, or conduct basic ecological studies, or perform applied environmental analyses, will find this guide useful for choosing the most appropriate medium, as well as in determining what limitations of benefits that choice might cause."--Jacket.